A Comparative Study on the Civil Relationship Between Fathers and Their Biological Children in Southeast Asia and the Middle East - Nabila Salma Amaliya (IHSA Institute, 2025)
Legally, every citizen possesses civil rights that must be protected. However, not all children are born into favorable circumstances. Some are born within lawful marriages, while others are born outside marital bonds. This study examines the civil relationship between fathers and their biological children in selected Southeast Asian countries, namely Indonesia and Malaysia, as well as Middle Eastern countries such as Kuwait and Morocco. The objective is to analyze the legal framework governing the status, rights, and obligations of fathers toward their biological children in these four jurisdictions. The research employs a normative juridical method with a qualitative and comparative approach. Findings reveal that in Indonesia, dualism exists among the Civil Code, the Marriage Law, and the Compilation of Islamic Law. In Malaysia, the civil relationship between a biological father and a child born out of wedlock is strictly limited under the National Fatwa Council and the Islamic Family Law Act, denying nasab, maintenance, and inheritance rights from the biological father. Similarly, Kuwaiti family law recognizes civil relations only through valid marriage. In Morocco, paternal civil relations are legally acknowledged solely when the child is born within a lawful marriage